Investigating the relationship between sustainability and farmer decision-making: a qualitative study of maize farmers in Mpumalanga, South Africa - Grewar, Robert (Rhodes University, Faculty of Commerce, Rhodes Business School, 2011)
The goal of the research paper was to understand the complex relationship between the issue of sustainability and maize farmers' decision-making processes. The aim is to shed light on the realities experienced by maize farmers in terms of how sustainability impacts on the decisions they make and how the decisions they make impact on sustainability. The importance of the research lies in the current state of affairs in the world in terms of the current economic recession, overpopulation, dire poverty and hunger, and the poor state of the environment. If humankind is to continue its existence on Earth in a happy, healthy world, something is going to have to give. In order for this to happen, people need to start grappling with the concept of sustainability. Focusing on sustainability as a whole is likely to end in despair. However, breaking the problem down into its component pieces will allow people to influence the particular sector in which they operate. It is therefore imperative for research into sustainability to be undertaken in all sectors of society and the economy. Agriculture presents an excellent research area due to its intrinsic link with the environment, society and the economy. Agriculture and its wellbeing is inextricably tied to environmental health. Healthy plants and animals will not grow in unhealthy conditions. Society is to a large degree dependent on agriculture for food, agriculture therefore has a significant impact on social order and function. Agriculture is one of the primary contributors to GDP, particularly in poor and developing nations. As a result, agriculture has an important role to play in ensuring economic sustainability. In order to engage with sustainability from an agricultural perspective it was decided to engage on the farmer-level. Gaining an understanding of their reality in terms of what motivates their decisions is key to understanding the relationship between agriculture and sustainability. Three maize farmers in Mpumalanga, South Africa, were interviewed with the aim of collecting qualitative data and then analysing the data using thematic analysis. The methodology employed enabled the researcher to uncover patterns in the data that constituted themes across the interviews. The following themes emerged: Theme 1: Economic factors are the primary decision driver. This is primarily due to the extent of the financial risk experienced by farmers as a result of market risk, production risk, finance risk, and rising input costs. This results in economic considerations superseding environmental or social concerns in farmers' decisions. This has a negative impact on the overall sustainability of the farming operation. Theme 2: There has been a decrease in the number of family-run farms. This is attributable to a number of factors including economic failure, fear of loss of land due to land-reform policies, as well as crime. Family-run farms tend to have a greater focus on sustainability due to the vested interest in the next generation taking over the farm. The corporate farming operations that are taking over the farms tend to be more focussed on short-term gains in order to satisfy shareholders. Theme 3: Mechanisation is preferable to manual labour. There has been an alarming decrease in the number of labourers employed on farms. Farmers say this is due to two factors. Firstly, machines are more efficient than labour. Secondly, restrictive labour laws have made famers less keen to employ people. The net effect of these two factors is that unemployment is rising. This has negative consequences for society, the economy, and the environment. Theme 4: Farmers believe they do very little environmental damage. This results in decisions being made that do not consider environmental wellbeing other than soil health. This is because farmers see healthy soil as an integral input that optimises economic performance. Farmers tend to prioritise economic factors in their decisions more than environmental or social factors. This results in an unsustainable perspective. The only ways in which this is likely to change is if the financial risk associated with agriculture is decreased, or if farmers are given financial incentive to change their ways. In order to deal with this issue it is necessary for further research to be conducted. Research needs to be conducted to confirm the results of this study. It is important to know whether the results pertain only to maize farmers in Mpumalanga or whether most farmers in South Africa, and indeed the world, face similar problems. Research should also be conducted to propose policies or procedures to reduce financial risk in agriculture. Research should focus on reducing market risk and reducing input costs, possibly via subsidisation.
Keywords: Sustainable agriculture -- Research -- South Africa; Agriculture -- South Africa -- Decision making; Corn -- Research -- South Africa